090. Effect of Turmeric Extract (Curcuma longa) on Granzyme Exoration and Tumour Mass Diameter Studi Pada Model Mencit Adenocarcinoma Mammae dengan Pemberian Kemoterapi Adriamycin Cyclophosphamide - Nugroho, Bachtiar Eko; Budijitno, Selamat (JBN (Jurnal Bedah Nasional); Vol 8 No 2 (2024): Proceeding The 2nd National Conference of Indonesia Surgical EducationDO - 10.24843/JBN.2024.v08.is02.p090, 2024)
Background : Breast cancer accounts for 11.6% of new cancer cases and 6.6% of cancer deaths. Treatment varies based on cancer type and stage, with Complementary Alternative Medicine (CAM) used as adjunct therapy. Turmeric (Curcuma longa) inhibits carcinogenesis, angiogenesis, and tumor growth. Granzyme, a protein involved in apoptosis, is a marker for immunity and tumor cell destruction. Methods : This in vivo experimental study used a Post Test Only Control Group Design. Twenty-five female Balb/c mice with DMBA-induced mammary adenocarcinoma were divided into five groups: positive control, negative control, and three treatment groups. Granzyme expression was measured through immunohistochemistry, and tumor diameters were assessed using calipers. Data were analyzed with SPSS. Results : The P3 group showed the highest granzyme expression (38.71 ± 18.20), while the K- group had the lowest (9.43 ± 3.25). The K- group had the largest tumor diameter (17.11 ± 3.28), and the P3 group had the smallest (10.55 ± 2.33). Granzyme expression significantly differed between groups (p = 0.022), with notable differences between the K- group and K+ (0.021), P1 (0.021), P2 (0.014), and P3 (0.021) groups. Significant differences were also found between the K+ group and the P1 (0.016), P2 (0.004), and P3 (0.014) groups. Conclusion : Granzyme expression was higher in the turmeric and chemotherapy treatment groups compared to the control groups, while tumor diameters were smaller, suggesting enhanced tumor suppression with turmeric extract.